2021
DOI: 10.1007/s00265-021-03030-3
|View full text |Cite
|
Sign up to set email alerts
|

Gregariousness is associated with parasite species richness in a community of wild chimpanzees

Abstract: Increased risk of pathogen transmission through proximity and contact is a well-documented cost of sociality. Affiliative social contact, however, is an integral part of primate group life and can benefit health. Despite its importance to the evolution and maintenance of sociality, the tradeoff between costs and benefits of social contact for group-living primate species remains poorly understood. To improve our understanding of this interplay, we used social network analysis to investigate whether contact via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In addition, degree and betweenness centrality predicted helminth infection in a proximity network of red-capped mangabeys ( Cercocebus torquatus ) [ 52 ]. Finally, strength in an association network based on same-subgroup membership predicted parasite richness in a group of chimpanzees ( Pan troglodytes ) [ 53 ]. Taken together, these studies appear to indicate a strong influence of individual differences in social-network position on parasite infection risk in primates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, degree and betweenness centrality predicted helminth infection in a proximity network of red-capped mangabeys ( Cercocebus torquatus ) [ 52 ]. Finally, strength in an association network based on same-subgroup membership predicted parasite richness in a group of chimpanzees ( Pan troglodytes ) [ 53 ]. Taken together, these studies appear to indicate a strong influence of individual differences in social-network position on parasite infection risk in primates.…”
Section: Introductionmentioning
confidence: 99%
“…We found group size to be associated with prevalence of some parasite taxa, mostly protozoans, which results from increased animal density and exposure risk amongst larger groups [ 78 ]. While sociality, the tendency to form social living groups, has many benefits for wild NHPs [ 79 ], increased risk of parasite infection is one well-documented cost [ 80 , 81 ], with spatial cohesion and contact between individual hosts facilitating parasite transmission [ 82 , 83 ]. Larger group size may also be associated with higher parasite prevalence due to increased resource competition between group members and social stress amongst host individuals [ 33 , 84 ] leading to poor nutrition and thus increased parasite susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Disease and social structure/network Several articles in this collection leverage social structure and network analyses to provide insights into the role of behavioral interactions on disease transmissibility. Deere et al (2021), for example, found that wild chimpanzees that spent more time with more individuals in the same area had higher helminth parasite richness, concluding that same shared space, rather than grooming contact, is responsible for higher parasitic risk. However, Lynsdale et al (2022) failed to find an association between gastrointestinal nematode load and sociality (measured by individual solitary behavior, work group size, and work group sex ratio) in semi-captive Asian elephants employed in timber logging.…”
Section: Sociality and Disease: Behavioral Perspectives In Ecological...mentioning
confidence: 99%